Electrode plate and preparation method thereof, battery and electric equipment
By designing the OI value difference of electrode active material in the center and edge areas in the electrode coating, and induced to form an ordered particle structure by using magnetic field to induced the formation of an inhomogeneous current density of the electrode sheet, the problem of uneven current density is solved, and the cycle life and performance of the battery are improved.
Patent Information
- Application Number
- CN202411644875.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-08-08
AI Technical Summary
The uneven current density of the electrode sheet causes problems such as lithium extraction and circulating diving during the cycle of the battery, which affects the cycle life of the battery.
By designing the OI values of the electrode active material in the central region and the edge region in the electrode coating, the OI value of the central region is smaller than the OI value of the edge region, forming an ordered electrode active material particle structure to optimize the current distribution.
It improves the current density uniformity of the electrode sheet during the battery cycle, reduces the battery impedance, and improves the battery cycle life and fast charging dynamics performance.
Smart Images

Figure CN120453269A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to an electrode sheet and a preparation method thereof, a battery and an electrical device. Background Art
[0002] Electrode sheets are a crucial component of batteries, and the electrode materials within them influence battery performance, including cycle life. In related technologies, lithium deposition and subsequent cycle failures are common during long battery cycles due to factors such as uneven current density within the electrode sheets, resulting in a short battery life and urgent need for solutions. Summary of the Invention
[0003] The present invention provides an electrode sheet and a preparation method thereof, a battery and an electrical device, which can effectively improve the cycle life and other performance of the battery and overcome the defects of the prior art.
[0004] In one aspect of the present invention, an electrode sheet is provided, comprising an electrode current collector and an electrode coating located on at least one side of the electrode current collector, wherein the electrode coating comprises an electrode active material; along the length direction of the electrode coating, the electrode coating comprises a central region and edge regions located on opposite sides of the central region, wherein the OI value of the electrode active material in the central region is less than the OI value of the electrode active material in the edge regions.
[0005] According to one embodiment of the present invention, the OI value of the electrode active material in the central region is 0.001-200, preferably 0.1-30; and / or the width of the central region in the length direction of the electrode coating is greater than or equal to 1 cm.
[0006] According to one embodiment of the present invention, each of the edge regions includes a plurality of sub-regions distributed along the length direction of the electrode coating, and in every two adjacent sub-regions, the OI value of the electrode active material of the sub-region close to the central region is smaller than the OI value of the electrode active material of the sub-region far from the central region.
[0007] According to one embodiment of the present invention, the ratio of the OI value of the electrode active material in the central region to the OI value of the electrode active material in the sub-region closest to the central region is 0.3 to 0.9; and / or, in each two adjacent sub-regions, the ratio of the OI value of the electrode active material in the sub-region close to the central region to the OI value of the electrode active material in the sub-region far from the central region is 0.3 to 0.9; and / or, the OI value of the electrode active material in any one of the sub-regions is 0.001 to 200, preferably 0.1 to 30; and / or, the width of any one of the sub-regions in the length direction of the electrode coating is greater than or equal to 1 cm.
[0008] According to one embodiment of the present invention, the length of the electrode coating is 1 cm to 10 m.
[0009] According to one embodiment of the present invention, the electrode sheet is a negative electrode sheet, and the electrode active material includes graphite.
[0010] According to one embodiment of the present invention, the electrode sheet is a positive electrode sheet, and the electrode active material includes a positive electrode ternary material and / or lithium iron phosphate.
[0011] According to one embodiment of the present invention, the porosity of the electrode coating is 20% to 40%; and / or the compaction density of the electrode coating is 1.3 g / cm 3 ~2g / cm 3 ; and / or, the surface density of the electrode coating is 200g / m 2 ~800g / m 2 .
[0012] Another aspect of the present invention provides a method for preparing the above-mentioned electrode sheet, comprising the following steps: applying a slurry containing the electrode active material to the surface of the electrode current collector to form a wet film on the surface of the electrode current collector; wherein, along the length direction of the electrode coating, the wet film includes a central area and edge areas located on opposite sides of the central area; then, applying a magnetic field of preset strength to the central area and edge areas of the wet film, respectively, and inducing the electrode active materials in the central area and edge areas of the wet film to reach preset OI values respectively through magnetic field induction; wherein, the strength of the magnetic field applied to the central area of the wet film is greater than the strength of the magnetic field applied to the edge areas of the wet film; then, drying and rolling are performed to obtain the electrode sheet.
[0013] According to one embodiment of the present invention, the intensity of the magnetic field applied to the central area of the wet film is 0.1T to 20T, preferably 0.2T to 2T.
[0014] According to one embodiment of the present invention, the edge area of the wet film includes a plurality of sub-areas distributed along the length direction of the wet film, and in every two adjacent sub-areas, the intensity of the magnetic field applied to the sub-area close to the central area is greater than the intensity of the magnetic field applied to the sub-area far from the central area.
[0015] According to one embodiment of the present invention, the intensity of the magnetic field applied to any one of the sub-regions of the wet film is 0.1T to 20T, preferably 0.2T to 2T.
[0016] Another aspect of the present invention provides a battery, comprising the electrode sheet or the electrode sheet prepared according to the method for preparing the electrode sheet.
[0017] According to one embodiment of the present invention, the battery includes a battery cell, the battery cell includes a positive electrode sheet and a negative electrode sheet, at least one of the positive electrode sheet and the negative electrode sheet is the above-mentioned electrode sheet or an electrode sheet prepared according to the above-mentioned electrode sheet preparation method; the positive electrode sheet includes a positive electrode tab, and the positive electrode tab is located at one end of the battery cell in the length direction; the negative electrode sheet includes a negative electrode tab, and the negative electrode tab is located at the other end of the battery cell in the length direction.
[0018] Another aspect of the present invention provides an electrical device comprising the battery.
[0019] The present invention provides an electrode sheet and a preparation method thereof, a battery, and an electrical device. In the electrode coating of the electrode sheet, the OI value of the electrode active material in the central region is lower than the OI value of the electrode active material in the edge region. By designing the OI value by region, the particle structure of the electrode active material in the electrode sheet is arranged in a manner that is conducive to uniform current distribution in the electrode sheet, thereby improving the impedance of different regions in the electrode sheet and balancing the current unevenness caused by uneven impedance in each region of the electrode sheet. This improves the current density uniformity of the electrode sheet during the battery cycle, avoids problems such as lithium plating and cycle drop due to uneven current density of the electrode sheet, and thus improves the cycle life and other performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a schematic structural diagram of an electrode sheet according to an embodiment of the present invention;
[0021] Figure 2 is a schematic plan view of an electrode coating according to an embodiment of the present invention;
[0022] Figure 3 is a cross-sectional SEM image of the negative electrode coating of Example 1;
[0023] Figure 4 is a cross-sectional SEM image of the negative electrode coating of Comparative Example 1;
[0024] Figure 5 Schematic diagram of the stacked structure of the positive electrode sheet, separator and negative electrode sheet in a battery cell according to an embodiment of the present invention.
[0025] Explanation of the figure marks: 1: electrode coating; 2: electrode current collector; 11: central area; 12: edge area; 121: 1st sub-area; 122: 2nd sub-area; 123: 3rd sub-area; L0: width of the central area; L1: width of the 1st sub-area; L2: width of the 2nd sub-area; L3: width of the 3rd sub-area; 101: first side 101; 102: second side 102; 3: positive electrode sheet; 31: positive electrode tab; 4: negative electrode sheet; 41: negative electrode tab; 5: diaphragm. DETAILED DESCRIPTION
[0026] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific embodiments listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts are within the scope of protection of the present invention.
[0027] In the related art, during the battery cycle, due to factors such as uneven current density of the electrode sheets, lithium deposition is prone to occur during long battery cycles, and the resulting cycle drop and other problems make the battery cycle life short, which urgently needs to be solved.
[0028] Specifically, the "rocking chair" energy storage mechanism of lithium batteries determines their relatively low power density. During the charging and discharging process, lithium ions need to repeatedly embed and extract between the positive and negative electrode materials. Therefore, the diffusion rate of lithium ions in the electrode active materials determines the battery's charging and discharging speed and other performance. At present, the main method is to shorten the diffusion path of lithium ions in the electrode active materials through structural design of the electrode materials, such as nano-sizing the electrode active materials and forming a porous structure. However, these methods are difficult to be applied in actual industrial production due to factors such as batch manufacturing cost considerations and process complexity.
[0029] After long-term research, the inventors of this application found that during the battery charge and discharge test, the electrode sheets generally have the problem of uneven current density. The reason for this is that due to factors such as the structure and preparation process of the electrode sheets, the impedance of different areas of the electrode sheets is usually different, which leads to uneven current density of the electrode sheets during the battery charge and discharge process. Specifically, the impedance of the central area of the electrode sheet in its longitudinal direction is usually higher than the impedance of the edge area, which makes the current density of the central area of the electrode sheet lower than the current density of the edge area, resulting in uneven current density of the electrode sheets during the battery charge and discharge process.
[0030] For example, electrode sheets are usually made by a coating method, that is, an electrode slurry used to form an electrode coating is coated on one side surface of an electrode current collector to form an electrode coating to make an electrode sheet. During the coating process, the electrode slurry has a certain fluidity, which inevitably causes differences in the thickness of different areas of the electrode coating, especially the thickness of the central area of the electrode coating is higher than the thickness of the edge area, which will cause the impedance of the central area to be greater than the impedance of the edge area, and then cause the current density of the central area to be lower than the current density of the edge area, making the current density of the electrode sheet uneven during battery charging and discharging.
[0031] For example, Figure 5 As shown, the electrode sheets in the battery cell include positive and negative sheets. The positive sheet includes a positive electrode tab, which is arranged at one end of the length direction of the battery cell. The negative sheet includes a negative electrode tab, which is arranged at the other end of the length direction of the battery cell. For the positive sheet or the negative sheet (hereinafter referred to as the electrode sheet), the impedance of the area closer to the tab is relatively smaller. Since the positive electrode tab and the negative electrode tab are respectively provided at the opposite ends of the length direction of the battery cell, the impedance of the edge area of the electrode sheet in its length direction is smaller than the impedance of its central area, and thus the current density in the central area of the electrode sheet is smaller than the current density in the edge area, resulting in uneven current density of the electrode sheet during the charging and discharging process of the battery.
[0032] Uneven current density across the electrode sheet can easily lead to surface lithium deposition and subsequent cycle drop during long battery cycles, impacting the battery's cycle life. Therefore, improving current density uniformity and, in turn, battery cycle life and other performance characteristics through rational electrode sheet structural design is a key challenge.
[0033] In view of this, an embodiment of the present invention provides an electrode sheet, such as Figure 1 and Figure 2 As shown, the electrode sheet includes an electrode current collector 2 and an electrode coating 1 located on at least one side surface of the electrode current collector 2, wherein the electrode coating 1 includes an electrode active material; along the length direction of the electrode coating 1, the electrode coating 1 includes a central region 11 and edge regions 12 located on opposite sides of the central region 11, and the OI value of the electrode active material in the central region 11 is less than the OI value of the electrode active material in the edge region 12.
[0034] According to the inventor's research and analysis, the OI values of different areas in the electrode coating 1 are different, which makes the orientation angles of the electrode active material particles in different areas of the electrode coating 1 different, and thus the lengths of the ion transmission channels formed are also different. Under the structural system of the above-mentioned electrode sheet, by controlling the OI value of the electrode active material in the central area 11 to be smaller than the OI value of the electrode active material in the edge area 12, the orientation degree of the electrode active material is regulated at the particle level in different regions, and constructing an electrode coating 1 with an orderly stacking of electrode active material particles and crystal structures in specific regions, the electrode sheet level performance can be improved, an ordered ion transmission channel can be formed, and the resistivity and ion diffusion capacity of the electrode sheet can be optimized, thereby improving the uneven current distribution at the battery level and the resulting poor battery cycle performance, thereby improving the cycle life of the battery, while reducing the battery impedance and improving the fast charging and dynamic performance of the battery.
[0035] Among them, by making the OI value of the electrode active material in the central area 11 lower than the OI value of the electrode active material in the edge area 12, the ion transmission capacity of the central area 11 can be improved, the electrical conductivity of the central area 11 can be improved, and the impedance of the central area of the electrode sheet is higher than the impedance of the edge area due to factors such as the structure of the electrode sheet and the coating process, and the resulting uneven current density of the electrode sheet can be improved. For example, the thickness of the central area of the electrode coating is greater than the thickness of the edge area due to factors such as the coating process, and the impedance of the central area is greater than the impedance of the edge area, and the current density of the central area is less than the current density of the edge area, which leads to uneven current density of the electrode sheet during battery charging and discharging. The problem of the impedance of the central area being greater than the impedance of the edge area due to the positive electrode tabs and the negative electrode tabs being respectively provided at the opposite ends of the length direction of the battery cell, and the current density of the central area being less than the current density of the edge area, and the resulting uneven current density of the electrode sheet during battery charging and discharging can be improved.
[0036] Continue to refer Figure 1 and Figure 2 The electrode sheet (electrode coating 1) has a first side 101 and a second side 102 opposite to each other in its length direction, and the electrode coating 1 is located in the middle position ( Figure 2 The distance from the outer edge of the first side 101 of the electrode coating 1 to the outer edge of the second side 102 of the electrode coating 1 is substantially equal to the distance from the outer edge of the second side 102 of the electrode coating 1, and the central area 11 of the electrode coating 1 is substantially divided into two halves by the middle position M of the electrode coating 1 (i.e., Figure 2 The dotted line M in the figure is the center line of the central area 11), that is, the central area 11 of the electrode coating 1 is the area extending from the middle position M of the electrode coating 1 to the first side 101 and the second side 102 by a distance L0 / 2, and L0 is the width of the central area 11 of the electrode coating 1 along the length direction of the electrode coating 1.
[0037] Continue to refer Figure 1 and Figure 2 , for the edge region 12 located on either side of the central region 11 of the electrode coating 1, it can be a sub-region. In this case, the electrode coating 1 includes a sub-region (edge region 12), the central region 11 and another sub-region (edge region 12) distributed in sequence along its length direction. For any sub-region, the OI values of its various regions are basically uniform.
[0038] In some preferred embodiments, Figure 1 and Figure 2As shown, for the edge region 12 located on either side of the central region 11 of the electrode coating 1, it includes multiple sub-regions distributed along the length direction of the electrode coating 1. In every two adjacent sub-regions, the OI value of the electrode active material in the sub-region close to the central region 11 is less than the OI value of the electrode active material in the sub-region away from the central region 11. At this time, the OI value of the electrode coating 1 tends to decrease gradually in the direction from the edge region 12 to the central region 11. In this way, by changing the orientation degree of the electrode active material particles at the particle level in different regions, it is beneficial to further improve the hierarchical performance of the electrode sheet, optimize the resistivity, ion diffusion capacity and other properties of the electrode sheet, thereby improving the problem of uneven current distribution at the battery level, and further improving the cycle life and other performance of the battery.
[0039] In the above-mentioned electrode sheet, the edge region 12 located on either side of the central region 11 of the electrode coating 1 extends to the outer edge of the electrode coating 1 in the longitudinal direction. Specifically, the edge region 12 is composed of n subregions, where n is an integer greater than or equal to 2, for example, n ≥ 3. The subregions distributed along the direction from the central region 11 to the edge region 12 of the electrode coating 1 are, in order, the first subregion 121, the second subregion 122, ..., and the nth subregion. The first subregion 121 is the subregion closest to the central region 11 of the electrode coating 1, and the nth subregion is the subregion farthest from the central region 11 of the electrode coating 1. The edge of the nth subregion facing away from the central region 11 is the outer edge of the electrode coating 1.
[0040] Among them, Figure 1 and Figure 2 As shown, the first sub-region 121 is in direct contact with the central region 11, and every two adjacent sub-regions are in direct contact. Specifically, the first sub-region 121 is a region extending from the cutoff edge of the central region 11 to a distance L1 in the direction away from the center line M (i.e., the width of the first sub-region 121 in the longitudinal direction of the electrode coating 1 is L1), the second sub-region 122 is a region extending from the cutoff edge of the first sub-region 121 to a distance L2 in the direction away from the center line M (i.e., the width of the second sub-region 122 in the longitudinal direction of the electrode coating 1 is L2), the third sub-region 123 is a region extending from the cutoff edge of the second sub-region 122 to a distance L3 in the direction away from the center line M (i.e., the width of the third sub-region 123 in the longitudinal direction of the electrode coating 1 is L3) ... The nth sub-region is a region extending from the cutoff edge of the n-1th sub-region to a distance L in the direction away from the center line M. n The width of the nth sub-region in the length direction of the electrode coating 1 is L n ), that is, the length of the electrode coating 1 L = L0 + 2 × (L1 + L2 + ... L n ).
[0041] For example, for the edge region 12 located on either side of the central region 11 of the electrode coating 1, the number of sub-regions can be 2 (n=2), 3 (n=3), 4 (n=4), 5 (n=5), 6 (n=6), etc., but is not limited thereto.
[0042] Relatively speaking, for the edge area 12 located on either side of the central area 11 of the electrode coating 1, the more sub-areas there are and the smaller the width of a single sub-area along the length direction of the electrode coating 1, the more conducive it is to improving the problem of uneven current distribution of the electrode sheet, and thus the more conducive it is to improving the cycle life and other performance of the battery. However, it will increase the difficulty of preparing the electrode sheet and the complexity of the preparation process to a certain extent. Therefore, considering the preparation process of the electrode sheet, battery performance and other factors, it is preferred that the width of any sub-area in the length direction of the electrode coating 1 is greater than or equal to 1 cm, for example, 1 cm, 10 cm, 30 cm, 50 cm, 80 cm, 100 cm, 120 cm, 140 cm, 150 cm, 180 cm, 200 cm, 230 cm, 250 cm, 500 cm, 800 cm, 1000 cm, 2000 cm, 3000 cm, 4000 cm, 5000 cm or a range consisting of any two of them.
[0043] In some embodiments, the length of the electrode coating 1 can be 1 cm to 10 m, preferably 10 cm to 5000 cm, for example, 1 cm, 10 cm, 30 cm, 50 cm, 80 cm, 100 cm, 120 cm, 140 cm, 150 cm, 180 cm, 200 cm, 230 cm, 250 cm, 500 cm, 800 cm, 1000 cm, 2000 cm, 3000 cm, 4000 cm, 5000 cm, or a range consisting of any two thereof. By making the OI value of the electrode active material in the central region 11 of the electrode coating 1 lower than the OI value of the electrode active material in the edge region 12, the problem of uneven current density of the electrode sheet during battery cycling can be improved, while facilitating the preparation of the electrode sheet and improving the preparation efficiency and yield of the electrode sheet.
[0044] Taking into further consideration the preparation process of the electrode sheet, battery performance and other factors, the width L0 of the central area 11 of the electrode coating 1 in the length direction of the electrode coating 1 can be greater than or equal to 1 cm, for example, 1 cm, 10 cm, 30 cm, 50 cm, 80 cm, 100 cm, 120 cm, 140 cm, 150 cm, 180 cm, 200 cm, 230 cm, 250 cm, 500 cm, 800 cm, 1000 cm, 2000 cm, 3000 cm, 4000 cm, 5000 cm or a range consisting of any two of them. This is beneficial to improve the current distribution uniformity of the electrode sheet while facilitating the preparation of the electrode sheet and improving the preparation efficiency and yield of the electrode sheet.
[0045] In the above electrode sheets, the electrode active material exists in the form of particles, such as Figure 1 As shown, the smaller the OI value of the electrode active material, the higher the verticality of the electrode active material particles, which helps reduce tortuosity, shorten the ion transmission path, and reduce ion transmission resistance. In the embodiment of the present invention, by designing different OI values for different regions, the OI value gradient of the electrode active material in the electrode coating 1 decreases from the edge of the electrode coating 1 toward the middle position M of the electrode coating 1, thereby causing the electrode active material particles (crystal structure) in the entire electrode coating 1 to be stacked in an orderly manner. This can effectively solve the problem of uneven current density of the electrode sheet during battery cycling, reduce the temperature difference between the center and edge areas of the electrode sheet, and improve the cycle life and other performance of the battery.
[0046] In the embodiment of the present invention, the shape of the electrode active material may be spherical, quasi-spherical, or other regular or irregular shapes.
[0047] Specifically, the OI value of the electrode active material in the central area 11 of the electrode coating 1 can be 0.001 to 200, for example, 0.001, 0.01, 0.1, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 30, 50, 80, 100, 130, 150, 180, 200 or a range consisting of any two of them, preferably 0.1 to 30, which is beneficial to further improve the current density uniformity of the electrode sheet during the battery cycle and improve the cycle life and other performance of the battery.
[0048] After further research, the ratio of the OI value of the electrode active material in the central area 11 of the electrode coating 1 to the OI value of the electrode active material in the sub-area closest to the central area 11 can be 0.3 to 0.9, for example, 0.3, 0.35, 0.38, 0.4, 0.43, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9 or a range composed of any two of them, which is beneficial to further improve the current density uniformity of the electrode sheet during the battery cycle, improve the cycle life of the battery and other performance, and at the same time facilitate the preparation of the electrode sheet and improve the preparation efficiency and yield of the electrode sheet.
[0049] In addition, in each two adjacent sub-regions, the ratio of the OI value of the electrode active material in the sub-region close to the central region 11 to the OI value of the electrode active material in the sub-region away from the central region 11 can be 0.3 to 0.9, for example, 0.3, 0.35, 0.38, 0.4, 0.43, 0.45, 0.5, 0.55, 0.6, 0.65, 0.67, 0.7, 0.75, 0.8, 0.85, 0.87, 0.9 or a range composed of any two of them, which is beneficial to further improve the current density uniformity of the electrode sheet during the battery cycle, improve the cycle life and other performance of the battery, and at the same time facilitate the preparation of the electrode sheet and improve the preparation efficiency and yield of the electrode sheet.
[0050] Specifically, the OI value of the electrode active material in any sub-region can be 0.001 to 200, preferably 0.1 to 30, which is beneficial to further improve the current density uniformity of the electrode sheet during battery cycling and improve battery performance such as cycle life.
[0051] In addition, the porosity of the above-mentioned electrode coating 1 can be 20% to 40%, for example, 20%, 21%, 23%, 25%, 28%, 30%, 31%, 33%, 35%, 38%, 40% or a range composed of any two of them, which is beneficial to further improve the cycle life and other performance of the battery.
[0052] In the embodiment of the present invention, the porosity of the electrode coating 1 on the electrode sheet can be measured by mercury intrusion porosimetry.
[0053] In addition, the compaction density of the electrode coating 1 can be 1.3 g / cm 3 ~2g / cm 3 , for example 1.3 g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3, 2g / cm 3 Or a range consisting of any two of them is beneficial to further improve the performance of the battery such as cycle life.
[0054] In addition, the surface density of the electrode coating 1 can be 200 g / m 2 ~800g / m 2 , for example 200g / m 2 , 210g / m 2 , 220g / m 2 , 230g / m 2 , 240g / m 2 , 250g / m 2 , 280g / m 2 , 300g / m 2 , 400g / m 2 , 500g / m 2 , 600g / m 2 , 700g / m 2 , 800g / m 2 Or a range consisting of any two of them is beneficial to further improve the performance of the battery such as cycle life.
[0055] In some embodiments, the above-mentioned electrode sheet can be a negative electrode sheet, and accordingly, the above-mentioned electrode current collector 2 is a negative electrode current collector, the electrode coating 1 is a negative electrode coating (negative electrode active material layer), and the above-mentioned electrode active material is a negative electrode active material, which may include graphite, for example, artificial graphite and / or natural graphite, and the electrode coating 1 may specifically include primary graphite particles and / or secondary graphite particles.
[0056] In an embodiment of the present invention, by controlling the OI value of the negative electrode active material (graphite) particles in the central area 11 of the negative electrode coating to be smaller than the OI value of the negative electrode active material (graphite) particles in the edge area 12, a negative electrode sheet with orderly stacked negative electrode active material particles and crystal structure is constructed, which can effectively improve the current density uniformity and other properties of the negative electrode sheet during the battery cycle, is beneficial to the performance of the negative electrode sheet under high surface density and compaction density, and improves the cycle life and other performance of the battery.
[0057] The embodiment of the present invention may adopt a conventional negative electrode current collector in the art, for example, the negative electrode current collector includes copper foil.
[0058] In other embodiments, the above-mentioned electrode sheet is a positive electrode sheet, and accordingly, the above-mentioned electrode current collector 2 is a positive electrode current collector, the electrode coating 1 is a positive electrode coating (positive electrode active material layer), and the electrode active material is a positive electrode active material, which may include a positive electrode ternary material and / or lithium iron phosphate, wherein the positive electrode ternary material, for example, includes a nickel-cobalt-manganese ternary material and / or a nickel-cobalt-aluminum ternary material.
[0059] In an embodiment of the present invention, by controlling the OI value of the positive electrode active material (such as lithium iron phosphate) particles in the central area 11 of the positive electrode coating to be smaller than the OI value of the positive electrode active material particles in the edge area 12, a positive electrode sheet with orderly stacked positive electrode active material particles and crystal structure is constructed. This can effectively improve the current density uniformity and other properties of the positive electrode sheet during the battery cycle, which is beneficial to the performance of the positive electrode sheet under high surface density and compaction density, and improves the cycle life and other properties of the battery.
[0060] The embodiment of the present invention may adopt a conventional positive electrode current collector in the art, for example, the positive electrode current collector includes aluminum foil.
[0061] In an embodiment of the present invention, an electrode coating 1 can be provided on one surface of the electrode collector 2, or an electrode coating 1 can be provided on the surfaces of both opposite sides of the electrode collector 2. When electrode coatings 1 are provided on both opposite surfaces of the electrode collector 2, the electrode coating 1 on one surface can be an electrode coating 1 designed for the OI values of the above-mentioned different regions (that is, the OI value of the electrode active material in the central region 11 is less than the OI value of the electrode active material in the edge region 12), or the electrode coatings 1 located on both opposite surfaces of the electrode collector 2 can be electrode coatings 1 designed for the OI values of the above-mentioned different regions.
[0062] Generally, the electrode coating 1 further comprises a conductive agent and a binder. Based on the total mass of the electrode coating 1, the mass fraction of the electrode active material (i.e., the ratio of the mass of the electrode active material to the total mass of the electrode coating 1) may be 70% to 99%, for example, 70%, 75%, 80%, 85%, 90%, 93%, 95%, 97%, 99% or a range consisting of any two thereof; the mass fraction of the conductive agent may be 0.5% to 15%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 8%, 10%, 13%, 15% or a range consisting of any two thereof; the mass fraction of the binder may be 0.5% to 15%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 8%, 10%, 13%, 15% or a range consisting of any two thereof.
[0063] In the embodiment of the present invention, the conductive agent in the electrode coating 1 can be a conventional conductive material in the art, for example, the conductive agent includes one or more of carbon black, carbon nanotubes (CNTs), acetylene black, graphene, Ketjen black, and carbon fiber.
[0064] In an embodiment of the present invention, the binder in the electrode coating 1 can be a conventional binding material in the art. For example, when the electrode sheet is a negative electrode sheet, the binder may include one or more of carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate; when the electrode sheet is a positive electrode sheet, the binder may include one or more of polyvinylidene fluoride (PVDF), polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, etc.
[0065] An embodiment of the present invention also provides a method for preparing the above-mentioned electrode sheet, comprising the following steps: applying a slurry containing electrode active material to the surface of an electrode current collector to form a wet film on the surface of the electrode current collector; wherein, along the length direction of the electrode coating, the wet film includes a central area and edge areas located on opposite sides of the central area; then, applying a magnetic field of preset strength to the central area and edge areas of the wet film, respectively, and inducing the electrode active materials in the central area and edge areas of the wet film to reach preset OI values respectively through the magnetic field; wherein, the strength of the magnetic field applied to the central area of the wet film is greater than the strength of the magnetic field applied to the edge area of the wet film; then, drying and rolling are performed to form the wet film into an electrode coating to obtain an electrode sheet.
[0066] During the preparation of the above-mentioned electrode sheet, the electrode active materials in each region are oriented and modified under different magnetic field intensities by magnetically inducing the orientation of the electrode active materials, so that the OI value of the electrode active material in the central region is smaller than the OI value of the electrode active material in the edge region. Combined with subsequent drying and rolling processes, an electrode sheet with an orderly stacked crystal structure of the electrode active materials in the electrode coating is obtained.
[0067] To give a further example, the negative electrode sheet is the main body of lithium storage, and graphite is usually used as the main negative electrode active material. Magnetic force is a non-contact force that can apply a magnetic field to the main graphite material to make it oriented and orderly arranged. Specifically, the orientation degree (OI value) of the graphite can be controlled by conditions such as the magnitude of the magnetic field strength applied to each region. By applying magnetic fields of different magnetic field strengths to different regions of the wet film, the graphite in each region is oriented under the magnetic field. The deflection angles of the graphite particles under different magnetic field strengths are different, so that the graphite in each region has different orientation degrees.
[0068] In an embodiment of the present invention, the magnetic field strength applied to the central area of the wet film is greater than the magnetic field strength applied to the edge area of the wet film, so that in the prepared electrode sheet, the OI value of the graphite in the central area of the electrode coating is smaller than the OI value of the graphite in the edge area. The graphite in the electrode coating forms an ordered ion transmission channel through the directional and ordered arrangement structure, which is beneficial to reducing the impedance of the electrode sheet and improving the problem of uneven current distribution of the electrode sheet during the battery cycle, thereby improving the cycle life and other performance of the battery.
[0069] Specifically, during the preparation of the negative electrode sheet, the intensity of the magnetic field applied to the central area of the wet film may be 0.1T to 20T, preferably 0.2T to 2T.
[0070] Specifically, the edge area of the wet film includes a plurality of sub-regions distributed along the length direction of the wet film, and in every two adjacent sub-regions, the intensity of the magnetic field applied to the sub-region close to the central area is greater than the intensity of the magnetic field applied to the sub-region away from the central area, so that in the prepared negative electrode sheet, the edge area of the electrode coating includes a plurality of sub-regions distributed along the length direction of the electrode coating, and in every two adjacent sub-regions, the OI value of the electrode active material in the sub-region close to the central area is less than the OI value of the electrode active material in the sub-region away from the central area.
[0071] Specifically, the intensity of the magnetic field applied to any sub-region of the wet film may be 0.1T to 20T, preferably 0.2T to 2T.
[0072] During the preparation process of the above-mentioned electrode sheet, after drying and rolling, the wet film on the surface of the electrode current collector forms an electrode coating, wherein the central area of the wet film forms the central area of the electrode coating, and the edge area of the wet film forms the edge area of the electrode coating. When the edge area of the wet film includes multiple sub-areas, the various sub-areas of the wet film correspondingly form various sub-areas of the electrode coating.
[0073] In an embodiment of the present invention, when electrode coatings are formed on both the front and back surfaces of an electrode current collector, a slurry containing an electrode active material can be first coated on one surface of the electrode current collector, and then induced in a magnetic field and dried. Then, a slurry containing an electrode active material is coated on the other surface of the electrode current collector, and then induced in a magnetic field and dried, and then rolled to obtain an electrode sheet.
[0074] In the embodiment of the present invention, a conventional magnetic field application method can be used to apply a magnetic field to various regions of the wet film. Specifically, a Gauss meter can be used to detect the surface of the wet film, and the measured value is the magnetic field intensity received by the wet film.
[0075] In the embodiment of the present invention, the drying (baking and drying) and roller pressing can also be conventional operations in the art and are not particularly limited thereto.
[0076] In an embodiment of the present invention, a slurry containing an electrode active material can be prepared by conventional methods in the art. For example, when the electrode sheet is a negative electrode sheet, the components for forming a negative electrode coating, such as a negative electrode active material, a conductive agent, and a binder, can be dispersed in a first solvent. The first solvent includes, for example, deionized water and / or N-methylpyrrolidone (NMP) to prepare a negative electrode slurry (i.e., a slurry containing an electrode active material), which is then applied to the surface of the negative electrode collector. After magnetic field induction, drying, rolling, and other processes, a negative electrode sheet is obtained. When the electrode sheet is a positive electrode sheet, the components for forming a positive electrode coating, such as a positive electrode active material, a conductive agent, and a binder, can be dispersed in a second solvent. The second solvent includes, for example, N-methylpyrrolidone (NMP), which is prepared to prepare a positive electrode slurry (i.e., a slurry containing an electrode active material), which is then applied to the surface of the positive electrode collector. After magnetic field induction, drying, rolling, and other processes, a positive electrode sheet is obtained.
[0077] In specific implementation, a slurry containing electrode active materials can be prepared at a temperature of 20-45° C.; the slurry containing electrode active materials can be coated on the surface of the electrode current collector using conventional coating equipment in the art, such as a continuous coating equipment.
[0078] An embodiment of the present invention further provides a battery, comprising the above-mentioned electrode sheet or an electrode sheet manufactured according to the above-mentioned method for manufacturing the electrode sheet. The battery has corresponding advantages to the above-mentioned electrode sheet, which will not be described in detail.
[0079] The battery of the embodiment of the present invention may be a lithium-ion battery (such as a lithium-ion power battery), a solar cell, or other new energy storage batteries.
[0080] Generally speaking, a battery includes an electrolyte, a cell, and a package that encapsulates the cell. The electrolyte is injected into the cell in the package, such as Figure 5 As shown, the battery cell includes a positive electrode sheet 3 , a negative electrode sheet 4 , and a separator 5 located between the positive electrode sheet 3 and the negative electrode sheet 4 .
[0081] In an embodiment of the present invention, at least one of the positive electrode sheet 3 and the negative electrode sheet 4 is an electrode sheet designed for the above-mentioned different region OI values, that is, the positive electrode sheet 3 can be an electrode sheet designed for the above-mentioned different region OI values (that is, the OI value of the positive electrode active material in the central region of the positive electrode coating is less than the OI value of the positive electrode active material in the edge region), or the negative electrode sheet 4 can be an electrode sheet designed for the above-mentioned different region OI values (that is, the OI value of the negative electrode active material in the central region of the negative electrode coating is less than the OI value of the negative electrode active material in the edge region), or both the positive electrode sheet 3 and the negative electrode sheet 4 are electrode sheets designed for the above-mentioned different region OI values.
[0082] Continue to refer Figure 5The positive electrode sheet 3 includes a positive electrode tab 31, which is connected to the positive electrode collector. The positive electrode tab 31 is arranged at one end of the positive electrode sheet 3 in the length direction (also the length direction of the positive electrode collector).
[0083] Continue to refer Figure 5 The negative electrode sheet 4 includes a negative electrode tab 41, which is connected to the negative electrode current collector. The negative electrode tab 41 is arranged at one end of the negative electrode sheet 4 in the longitudinal direction (also the longitudinal direction of the negative electrode current collector).
[0084] Continue to refer Figure 5 In the battery cell, the positive electrode tab 31 and the negative electrode tab 41 are located at opposite ends of the length direction of the battery cell. That is, the positive electrode tab 31 is located at one end of the length direction of the battery cell, and the negative electrode tab 41 is located at the other end of the length direction of the battery cell. The length direction of the battery cell, the length direction of the positive electrode sheet 3, and the length direction of the negative electrode sheet 4 are parallel to each other.
[0085] In the embodiment of the present invention, the positive electrode tab 31 can be provided on the positive electrode sheet 3 by conventional methods in the art. For example, the positive electrode tab 31 is welded to the positive electrode current collector or extended outward from the positive electrode current collector. There is no particular limitation on this.
[0086] In the embodiment of the present invention, the negative electrode tab 41 can be provided on the negative electrode sheet 4 by conventional methods in the art. For example, the negative electrode tab 41 is welded to the negative electrode current collector or extended outward from the negative electrode current collector. There is no particular limitation on this.
[0087] Specifically, the battery cell may be a laminated battery cell, that is, the battery cell is formed by alternating and stacking the positive electrode sheet 3 , the separator 5 and the negative electrode sheet 4 .
[0088] The electrolyte of the embodiment of the present invention can be a conventional electrolyte in the field. For example, the electrolyte is a non-aqueous electrolyte, which can specifically include an organic solvent and an electrolyte salt. The organic solvent includes, for example, ethylene carbonate and / or diethyl carbonate. When the battery is a sodium ion battery, the electrolyte salt can include a lithium salt. The lithium salt includes, for example, lithium hexafluorophosphate (LiPF6), etc., but is not limited thereto.
[0089] In the embodiment of the present invention, the separator 5 is used to separate the positive electrode sheet 3 and the negative electrode sheet 4 to prevent the positive electrode sheet 3 and the negative electrode sheet 4 from short-circuiting. The embodiment of the present invention can adopt conventional separators in the art without special limitation.
[0090] In the embodiment of the present invention, conventional packaging (shell) materials in the art may be used to encapsulate the battery cells, and the battery may be of a conventional battery type and structure in the art. For example, the battery may be a blade battery, but is not limited thereto.
[0091] In the embodiment of the present invention, the positive electrode sheet 3 , the separator 5 , the negative electrode sheet 4 and other components can be assembled into a battery by conventional methods in the art, and there is no particular limitation on this.
[0092] An embodiment of the present invention further provides an electrical device including the above-mentioned battery. The electrical device has advantages corresponding to those of the above-mentioned electrode sheet, which will not be described in detail.
[0093] The electrical equipment in the embodiments of the present invention can be conventional electrical equipment in this field, such as power equipment (such as electric vehicles, electric cars), electronic equipment (such as mobile phones, tablets, laptops, digital cameras, etc.), wearable devices (such as watches, bracelets, VR glasses, etc.), energy storage power stations, etc., without special restrictions.
[0094] In an embodiment of the present invention, the position and width of the central region and each sub-region in the electrode coating, as well as the number of sub-regions and other characteristics can be measured by scanning electron microscopy (SEM), XRD analysis, etc. For example, the surface of the electrode coating is detected by SEM, and based on the different grayscale and color (such as blacker or whiter, etc.) presented by each region, the position and width of the central region, the number of sub-regions, the position and width of each sub-region and other characteristics are determined. Alternatively, the OI values of different regions can be tested by XRD, and the different regions of the electrode coating can be determined based on the OI value measurement results.
[0095] In an embodiment of the present invention, X-ray diffraction (XRD) analysis can be performed on each region of the electrode coating to measure the OI value of the electrode active material in each region. Taking the OI value of the negative electrode active material as an example, the OI value represents the orientation of the crystal structure of the negative electrode active material particles. In the XRD analysis results of a certain region of the electrode coating, I1 is the XRD peak intensity in the direction in which active ions (such as lithium ions) are embedded in the crystal structure of the negative electrode active material particles, and I2 is the XRD peak intensity in the crystal direction perpendicular to I1 and in which active ions are more difficult to embed (that is, the crystal direction in which active ions are more difficult to embed is perpendicular to the crystal structure direction in which active ions are embedded in the negative electrode active material particles). Then, the crystal structure orientation value within the negative electrode active material particles (i.e., the OI value of the negative electrode active material) = I2 / I1, and the OI value is greater than 0. Taking the negative electrode sheet using graphite as the negative electrode active material as an example, XRD analysis was performed on each area of the negative electrode coating. In the XRD analysis results, I1 is the peak intensity of the 110 crystal direction of graphite, I2 is the peak intensity of the 004 crystal direction of graphite, and the OI value of graphite = I2 / I1. The OI value of graphite can be used to characterize the arrangement order of the crystal structure of the graphite particles (the smaller the OI value, the higher the order (verticality)).
[0096] In addition, taking the positive electrode sheet using lithium iron phosphate as the positive electrode active material as an example, XRD analysis was performed on various areas of the positive electrode coating. In the XRD analysis results, I1 is the peak intensity of the 020 crystal direction of lithium iron phosphate, I2 is the peak intensity of the 200 crystal direction of lithium iron phosphate, and the OI value of lithium iron phosphate = I2 / I1.
[0097] In an embodiment of the present invention, the testing process of the surface density of the electrode coating may include: taking an electrode sheet sample, testing the total mass m1 of the electrode sheet sample, and the surface area S of a single side in the thickness direction of the electrode sheet sample; then scraping the electrode coating on the electrode sheet sample, and testing the mass m2 of the electrode current collector obtained, then the surface density of the electrode coating = (m1-m2) / S.
[0098] In an embodiment of the present invention, the compacted density of the electrode coating = the surface density of the electrode coating / the total thickness of the electrode coating, wherein the testing process of the surface density of the electrode coating refers to the above, and the testing process of the total thickness of the electrode coating may include: taking an electrode sheet sample, testing the total thickness T1 of the electrode sheet sample (T1 = the total thickness of the electrode coating + the thickness of the electrode collector. When the front and back surfaces of the electrode collector are respectively provided with electrode coatings, the total thickness of the electrode coating = the thickness of the electrode coating located on one surface of the electrode collector + the thickness of the electrode coating located on the other surface of the electrode collector); then scraping off the electrode coating on the electrode sheet sample, testing the thickness T2 of the electrode collector, and the total thickness of the electrode coating = T1-T2.
[0099] In specific implementation, a micrometer can be used to measure the average thickness T1 of the electrode sheet and the average thickness T2 of the electrode current collector.
[0100] In a specific implementation, the battery can be disassembled to obtain the electrode sheet, and then the OI values of different areas in the electrode coating of the electrode sheet, as well as the surface density and compaction density of the electrode coating and other characteristics are tested.
[0101] The present invention is further described below by way of specific examples. In the following examples, the magnetic field strength, the surface density and compacted density of the electrode coating, the XRD test of graphite (graphite OI value = I2 / I1, I1 is the peak intensity of the 110 crystal direction of graphite, I2 is the peak intensity of the 004 crystal direction of graphite), the XRD test of lithium iron phosphate (lithium iron phosphate OI value = I2 / I1, I1 is the peak intensity of the 020 crystal direction of lithium iron phosphate, I2 is the peak intensity of the 200 crystal direction of lithium iron phosphate), and other related test processes are referred to above and will not be repeated here.
[0102] Example 1
[0103] 1. Preparation of negative electrode sheet
[0104] (1) Graphite, carbon black, CMC, and SBR were mixed in a mass ratio of 100:1:1.6:3.3, and deionized water and NMP were added and stirred to prepare a negative electrode slurry;
[0105] (2) A continuous coating device is used to coat the negative electrode slurry on one surface of the copper foil, and a magnetic field with a magnetic field strength of H0 = 0.552T is applied to the central area of the formed wet film (width L0 = 50cm), a magnetic field with a magnetic field strength of H1 = 0.38T is applied to the first sub-area (width L1 = 150cm) closest to the central area of the wet film, a magnetic field with a magnetic field strength of H2 = 0.254T is applied to the second sub-area (width L2 = 230cm) located on the side of the first sub-area away from the central area, and a magnetic field with a magnetic field strength of H3 = 0.119T is applied to the third sub-area (L3 = 140cm) located on the side of the second sub-area away from the central area. The orientation of the graphite in each area is induced by the applied magnetic field. The induction time is about 5 minutes. The magnetic field is kept uniform and stable during the induction period. After the induction is completed, the wet film is dried to form a coating layer; wherein, Figure 2 As shown, the first sub-region, the second sub-region and the third sub-region are respectively present on opposite sides of the central region. During the magnetic field induction process, a magnetic field is applied to each sub-region according to the above magnetic field strength for induction.
[0106] (3) Then, the coating, magnetic field induction and drying processes of the above step (2) are repeated on the other side of the copper foil to form a coating layer on both the front and back surfaces of the copper foil, and then the copper foil is rolled to obtain a negative electrode sheet with a negative electrode coating formed on both the front and back surfaces of the copper foil.
[0107] Among them, the structure of the negative electrode is as follows Figure 1 and Figure 2 As shown, the negative electrode coating located on the surface of either side of the copper foil includes a central area 11 and edge areas 12 located on opposite sides of the central area. For the edge area 12 located on either side of the central area, it has three sub-areas, namely the first sub-area 121, the second sub-area 122, and the third sub-area 123 distributed in sequence along the direction from the central area 11 to the edge area 12 (the outer edge of the third sub-area 123 away from the central area is the outer edge of the negative electrode coating on one side of its length direction). The length of the central area 11 along the width direction of the positive electrode coating and the length of each sub-area along the width direction of the positive electrode coating are basically equal to the width of the negative electrode sheet.
[0108] Among them, the width L0 of the central area 11 of the negative electrode coating along the length direction of the negative electrode coating is 50 cm, the width L1 of the first sub-area 121 along the length direction of the negative electrode coating is 150 cm, the width L2 of the second sub-area 122 along the length direction of the negative electrode coating is 230 cm, and the width L3 of the third sub-area 123 along the length direction of the negative electrode coating is 140 cm.
[0109] Among them, the OI value of the graphite in each area of the negative electrode coating, the surface density of the negative electrode coating, the compaction density of the negative electrode coating, and the porosity of the negative electrode coating are shown in Table 1.
[0110] 2. Preparation of positive electrode
[0111] Lithium iron phosphate, CNT, carbon black, and PVDF were mixed in a mass ratio of 100:0.3:0.5:2.5, and NMP was added and stirred evenly to prepare a positive electrode slurry;
[0112] The positive electrode slurry is coated on the front and back surfaces of the aluminum foil, and after drying and rolling, a positive electrode coating is formed on the front and back surfaces of the aluminum foil to prepare a positive electrode sheet; wherein the surface density of the positive electrode coating is 500g / m 2 .
[0113] 3. Battery assembly
[0114] The positive electrode sheets, separators and negative electrode sheets are alternately stacked to form a laminated battery cell, and the electrolyte is injected to assemble a soft pack battery (the battery design capacity is 120Ah); wherein the composition of the electrolyte used is as follows: the organic solvent is a mixture of ethylene carbonate and diethyl carbonate in a volume ratio of 1:1, and the LiPF6 concentration in the electrolyte is 1 mol / L. The stacked structure of the positive electrode sheet 3, separator 5 and negative electrode sheet 4 in the laminated battery cell is as follows: Figure 5 As shown, the positive electrode tab 31 of the positive electrode sheet 3 is located at one end of the battery cell in the length direction, and the negative electrode tab 41 of the negative electrode sheet 4 is located at the other end of the battery cell in the length direction.
[0115] Example 2: The difference from Example 1 is that the magnetic field strength applied to the central area of the wet film is H0 = 0.431T, the magnetic field strength applied to the first sub-area is H1 = 0.32T, the magnetic field strength applied to the second sub-area is H2 = 0.263T, and the magnetic field strength applied to the third sub-area is H3 = 0.1T. In the prepared electrode sheet, the OI value of the graphite in each area of the negative electrode coating is shown in Table 1; the remaining steps and conditions are the same as in Example 1.
[0116] Example 3: The difference from Example 1 is that the magnetic field strength applied to the central area of the wet film is H0 = 0.33T, the magnetic field strength applied to the first sub-area is H1 = 0.272T, the magnetic field strength applied to the second sub-area is H2 = 0.16T, and the magnetic field strength applied to the third sub-area is H3 = 0T. In the prepared electrode sheet, the OI value of the graphite in each area of the negative electrode coating is shown in Table 1; the remaining steps and conditions are the same as in Example 1.
[0117] Comparative Example 1: The difference from Example 1 is that no magnetic field is applied during the preparation of the negative electrode sheet (i.e., in Comparative Example 1, the negative electrode slurry is coated on both the front and back surfaces of the copper foil, and then dried and rolled to form a negative electrode coating to prepare the negative electrode sheet); the remaining steps and conditions are the same as in Example 1.
[0118] Comparative Example 2: The difference from Example 1 is that, during the preparation of the negative electrode sheet, the magnetic field strength H0 applied to the central area of the wet film is 0.1T, the magnetic field strength H1 applied to the first sub-area is 0.263T, the magnetic field strength H2 applied to the second sub-area is 0.32T, and the magnetic field strength H3 applied to the third sub-area is 0.431T. In the prepared negative electrode sheet, the OI value of the graphite in each area of the negative electrode coating is shown in Table 1; the remaining steps and conditions are the same as in Example 1.
[0119] Comparative Example 3: The difference from Example 1 is that during the preparation of the negative electrode sheet, the same magnetic field with a magnetic field strength of 0.36 T is applied to the entire area of the wet film, so that the OI value of the graphite in each area of the formed negative electrode coating is basically the same (the OI value of the graphite in each area is about 20.2, see Table 1 for details); the remaining steps and conditions are the same as in Example 1.
[0120] Example 4
[0121] The difference between Example 4 and Example 1 is that a magnetic field is applied during the preparation of the positive electrode sheet, but no magnetic field is applied during the preparation of the negative electrode sheet. The remaining steps and conditions are the same as those in Example 1.
[0122] The preparation process of the positive electrode sheet and the negative electrode sheet of this embodiment 4 is as follows:
[0123] 1. Preparation of negative electrode sheet
[0124] Graphite, carbon black, CMC, and SBR were mixed in a mass ratio of 100:1:1.6:3.3, and deionized water and NMP were added and stirred evenly to prepare a negative electrode slurry;
[0125] The negative electrode slurry is coated on the front and back surfaces of the copper foil. After drying and roller pressing, a negative electrode coating is formed on the front and back surfaces of the copper foil to produce a negative electrode sheet.
[0126] 2. Preparation of positive electrode
[0127] (1) Lithium iron phosphate, CNT, carbon black, and PVDF were mixed in a mass ratio of 100:0.3:0.5:2.5, and NMP was added and stirred evenly to prepare a positive electrode slurry;
[0128] (2) A continuous coating device is used to coat the positive electrode slurry on one side of the aluminum foil, and a magnetic field with a magnetic field strength of H0 = 0.552T is applied to the central area of the formed wet film (width L0 = 50cm), a magnetic field with a magnetic field strength of H1 = 0.38T is applied to the first sub-area (width L1 = 150cm) closest to the central area of the wet film, a magnetic field with a magnetic field strength of H2 = 0.254T is applied to the second sub-area (width L2 = 230cm) located on the side of the first sub-area away from the central area, and a magnetic field with a magnetic field strength of H3 = 0.119T is applied to the third sub-area (L3 = 140cm) located on the side of the second sub-area away from the central area. The orientation of the graphite in each area is induced by the applied magnetic field. The induction time is about 5 minutes. The magnetic field is kept uniform and stable during the induction period. After the induction is completed, the wet film is dried to form a coating layer.
[0129] (3) Then, the coating, magnetic field induction and drying processes of the above step (2) are repeated on the other side surface of the aluminum foil to form a coating layer on both the front and back surfaces of the aluminum foil, and then the aluminum foil is rolled to obtain a positive electrode sheet with a positive electrode coating formed on both the front and back surfaces of the aluminum foil.
[0130] Among them, the structure of the positive electrode is as follows Figure 1 and Figure 2 As shown, the positive electrode coating located on the surface of either side of the aluminum foil includes a central area 11 and edge areas 12 located on opposite sides of the central area 11. For the edge area 12 located on either side of the central area 11, it has three sub-areas, namely the first sub-area 121, the second sub-area 122, and the third sub-area 123 distributed in sequence along the direction from the central area 11 to the edge area 12 (the outer edge of the third sub-area 123 away from the central area 11 is the outer edge of the positive electrode coating on one side of its length direction). The length of the central area 11 along the width direction of the positive electrode coating and the length of each sub-area along the width direction of the positive electrode coating are basically equal to the width of the positive electrode sheet.
[0131] Among them, the width L0 of the central area 11 of the positive electrode coating along the length direction of the positive electrode coating is 50 cm, the width L1 of the first sub-area 121 along the length direction of the positive electrode coating is 150 cm, the width L2 of the second sub-area 122 along the length direction of the positive electrode coating is 230 cm, and the width L3 of the third sub-area 123 along the length direction of the positive electrode coating is 140 cm.
[0132] Among them, the OI value of lithium iron phosphate in each area of the positive electrode coating, the surface density of the positive electrode coating, the compaction density of the positive electrode coating, and the porosity of the positive electrode coating are shown in Table 2.
[0133] Comparative Example 4: The difference from Example 4 is that no magnetic field is applied during the preparation of the positive electrode sheet (i.e., in Comparative Example 3, the positive electrode slurry is coated on both the front and back surfaces of the copper foil, and then dried and rolled to form a positive electrode coating to prepare the positive electrode sheet); the remaining steps and conditions are the same as in Example 4.
[0134] Comparative Example 5: The difference from Example 4 is that, during the preparation of the positive electrode sheet, the magnetic field strength H0 applied to the central area of the wet film is 0.1T, the magnetic field strength H1 applied to the first sub-area is 0.263T, the magnetic field strength H2 applied to the second sub-area is 0.32T, and the magnetic field strength H3 applied to the third sub-area is 0.431T. In the prepared positive electrode sheet, the OI value of the lithium iron phosphate in each area of the positive electrode coating is shown in Table 2; the remaining steps and conditions are the same as in Example 4.
[0135] Comparative Example 6: The difference from Example 4 is that during the preparation of the positive electrode sheet, the same magnetic field with a magnetic field strength of 0.32 T is applied to the entire area of the wet film, so that the OI values of the lithium iron phosphate in each area of the formed negative electrode coating are basically the same (the OI values of the lithium iron phosphate in each area are about 3.2, see Table 2 for details); the remaining steps and conditions are the same as in Example 1.
[0136] The DC impedance (DCIR) and long cycle performance (number of cycles when the capacity decays to 80%) of the batteries of each embodiment and comparative example were tested according to the following process. The results are shown in Tables 1 and 2.
[0137] (1) 50% SOC DC internal resistance test: At 25°C, the state of charge of the above-mentioned soft-pack battery was adjusted to 50% SOC, and then charged at 1.5C for 30s. The voltage drop of the soft-pack battery was recorded to calculate its DC resistance DCIR.
[0138] (2) Long cycle test: At 25°C, discharge at 0.5C constant current to 2.0V, charge at 0.5C constant current to 3.8V, and charge at 0.2C constant current to 3.8V. Continue cycling until the SOC reaches 80% of the original value. Record the number of cycles (see the long cycle numbers in Tables 1 and 2).
[0139] Table 1
[0140] Example Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 <![CDATA[Areal density of the negative electrode coating (g / m 2 )]]> 230.5 230.6 230.8 230.6 230.6 230.6 <![CDATA[Compaction density of the negative electrode coating (g / cm 3 )]]> 1.61 1.60 1.60 1.60 1.60 1.61 Porosity of the negative electrode coating 30.5% 30.6% 30.5% 30.4% 30.4% 30.2% Graphite OI value in the central area 5.42 7.46 8.95 38.12 26.89 20.12 Graphite OI value of the first sub-area 15.43 17.24 20.38 38.08 23.48 20.22 Graphite OI value of the second sub-area 23.55 25.66 26.98 38.48 15.23 20.16 Graphite OI value of the third sub-area 26.94 28.32 38.22 38.36 5.37 20.11 DC internal resistance (mΩ) 66.8 70.5 75.4 86.2 66.9 67.45 Long cycle number (laps) 2868 2430 2236 1932 1689 2163
[0141] Table 2
[0142] Example Example 4 Comparative Example 4 Comparative Example 5 Comparative Example 6 <![CDATA[Areal density of the positive electrode coating (g / m 2 )]]> 499.8 499.9 500.1 499.8 <![CDATA[The tap density of the positive electrode coating (g / cm 3 )]]> 2.58 2.58 2.58 2.58 Porosity of the cathode coating 20.8% 21% 21% 21% Lithium iron phosphate OI value in the central area 0.20 0.52 0.48 0.32 Lithium iron phosphate OI value in the first sub-area 0.28 0.52 0.40 0.31 Lithium iron phosphate OI value in the second sub-area 0.33 0.53 0.33 0.32 Lithium iron phosphate OI value in the third sub-area 0.41 0.53 0.28 0.33 DC internal resistance (mΩ) 69.2 87.3 68.9 66.21 Long cycle number (laps) 2382 1860 1602 1920
[0143] As can be seen from Table 1, compared with Comparative Example 1, Examples 1 to 3 regionally regulate the OI value of the negative electrode sheet, so that the OI value of the graphite of the negative electrode coating decreases gradually from the edge area to the center area, which can significantly reduce the DC internal resistance of the battery and improve the long cycle life of the battery. At the same time, it can be seen from Examples 1 to 3 that the lower the OI value of the graphite in each area, the lower the DC internal resistance of the battery and the better the long cycle effect.
[0144] In addition, it can be seen from Example 1 and Comparative Example 2 that the graphite OI value in the negative electrode sheet of Comparative Example 2 is designed in the opposite direction to that of Example 1 (the graphite OI value of the negative electrode coating increases gradually from the edge area to the center area), and its cycle performance is greatly reduced. Compared with Comparative Example 2, the long cycle life of Example 1 is significantly improved. The reason for this is that in Example 1, by controlling the graphite OI value of the central area 11 to be smaller than the graphite OI value of the edge area 12, the ion transmission capacity of the central area 11 can be improved, the conductivity of the central area 11 can be reduced, and the problem that the impedance of the central area 11 of the negative electrode sheet is higher than the impedance of the edge area 12 due to factors such as the structure of the negative electrode sheet and the coating process, and the resulting uneven current density of the negative electrode sheet can be improved. Specifically, the problem that the thickness of the central area 11 of the negative electrode coating is greater than the thickness of the edge area 12 due to factors such as the coating process, thereby making the impedance of the central area 11 greater than that of the edge area 12, can be improved. The present invention solves the problems of the impedance of the central region 11 being greater than the impedance of the edge region 12, and the current density of the central region 11 being less than the current density of the edge region 12, which in turn causes the current density of the negative electrode sheet to be uneven during the battery charge and discharge process. It also improves the problems of the impedance of the central region 11 being greater than the impedance of the edge region 12, which in turn causes the current density of the central region 11 to be less than the current density of the edge region 12, and the current density of the negative electrode sheet to be uneven during the battery charge and discharge process, due to the positive and negative electrode tabs being provided at the opposite ends of the length direction of the battery cell, while the central region 11 is not provided with tabs. The battery cycle life and other performance are improved. However, the reverse design of Comparative Example 2 makes it difficult to reduce the impedance of the central region 11 and balance the current density of the central region 11 and the edge region 12. It cannot effectively overcome the problem of uneven current distribution of the negative electrode sheet during the battery charge and discharge process. Therefore, the cycle life of the battery is poor.
[0145] In addition, in Comparative Example 3, during the preparation of the negative electrode sheet, the same magnetic field was applied to each area of the wet film used to form the negative electrode coating, so as to induce the reduction of the OI value of the graphite in the negative electrode coating through the magnetic field. Although the internal resistance of the battery can be reduced to a certain extent, the OI values of the graphite in each area of the negative electrode coating are basically the same (all around 20.2). Due to problems such as uneven current distribution of the negative electrode coating during the battery charging and discharging process, the cycle life of the battery is poor. Compared with Comparative Example 3, Examples 1 to 3 can significantly improve the cycle life of the battery while maintaining a low internal resistance of the battery.
[0146] Taking Example 1 and Comparative Example 1 as examples, the cross-sections of the negative electrode coating in Example 1 and the negative electrode coating in Comparative Example 1 were observed using an electron microscope (SEM) (the arrangement of graphite particles in the negative electrode coating was observed by SEM). The cross-section SEM image of the negative electrode coating in Example 1 was shown in FIG. Figure 3 The cross-sectional SEM image of the negative electrode coating of Comparative Example 1 is shown in FIG. Figure 4 ,from Figure 3 and Figure 4 It can be seen that the deflection angles of the graphite particles in the negative electrode coating of Example 1 and Comparative Example 1 are significantly different. The verticality of the graphite particles in the negative electrode coating of Example 1 is significantly improved, and the tortuosity is reduced, so that the resistivity and liquid phase diffusion resistance of the electrode sheet are reduced, thereby reducing the impedance, and improving the current distribution uniformity of the electrode sheet during the battery cycle, thereby improving the cycle life and other performance of the battery.
[0147] As can be seen from Table 2, compared with Comparative Example 4, Example 4 regionally regulates the OI value of the positive electrode sheet, so that the OI value of the lithium iron phosphate of the positive electrode coating decreases gradually from the edge area to the center area, which can significantly reduce the DC internal resistance of the battery and improve the long cycle life of the battery.
[0148] In addition, it can be seen from Example 4 and Comparative Example 5 that the OI value of the lithium iron phosphate in the positive electrode sheet of Comparative Example 5 is designed in the opposite direction to that of Example 4 (the OI value of the lithium iron phosphate of the positive electrode coating increases in a gradient from the edge area to the center area), and its cycle performance is greatly reduced. Compared with Comparative Example 4, the long cycle life of Example 4 is significantly improved. The reason for this is that in Example 1, by controlling the OI value of the lithium iron phosphate in the central area 11 to be less than the OI value of the lithium iron phosphate in the edge area 12, the ion transmission capacity of the central area 11 can be improved, the conductivity of the central area 11 can be reduced, and the problem of the impedance of the central area 11 of the positive electrode sheet being higher than the impedance of the edge area 12 due to factors such as the structure of the positive electrode sheet and the coating process, and the resulting uneven current density of the positive electrode sheet can be improved. Specifically, the problem of the thickness of the central area 11 of the positive electrode coating being greater than the thickness of the edge area 12 due to factors such as the coating process can be improved, thereby making the impedance of the central area 11 greater than that of the edge area The present invention solves the problems of the impedance of the central region 11 being greater than the impedance of the edge region 12, and the current density of the central region 11 being less than the current density of the edge region 12, which in turn leads to uneven current density of the positive electrode sheet during the battery charging and discharging process. The present invention also improves the problems of the impedance of the central region 11 being greater than the impedance of the edge region 12, which in turn leads to the current density of the central region 11 being less than the current density of the edge region 12, and the uneven current density of the positive electrode sheet during the battery charging and discharging process, due to the positive electrode tabs and negative electrode tabs being respectively provided at the opposite ends of the length direction of the battery cell, while the central region 11 is not provided with tabs. The battery cycle life and other performance are improved. However, the reverse design of Comparative Example 2 makes it difficult to reduce the impedance of the central region 11 and balance the current density of the central region 11 and the edge region 12. It cannot effectively overcome the problem of uneven current distribution of the positive electrode sheet during the battery charging and discharging process. Therefore, the cycle life of the battery is poor.
[0149] In addition, in Comparative Example 6, during the preparation of the negative electrode sheet, the same magnetic field was applied to each area of the wet film used to form the positive electrode coating, so as to induce the reduction of the OI value of the lithium iron phosphate in the positive electrode coating through the magnetic field. Although the internal resistance of the battery can be reduced to a certain extent, the OI values of the lithium iron phosphate in each area of the positive electrode coating are basically the same (all around 0.32). Due to problems such as uneven current distribution of the positive electrode coating during the battery charging and discharging process, the cycle life of the battery is poor. Compared with Comparative Example 6, Example 4 can significantly improve the cycle life of the battery while maintaining a lower internal resistance of the battery.
[0150] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An electrode sheet, characterized in that: The invention comprises an electrode current collector and an electrode coating located on at least one side of the electrode current collector, wherein the electrode coating comprises an electrode active material; Along the length direction of the electrode coating, the electrode coating includes a central region and edge regions located on opposite sides of the central region, and the OI value of the electrode active material in the central region is smaller than the OI value of the electrode active material in the edge regions.
2. The electrode sheet according to claim 1, characterized in that The OI value of the electrode active material in the central region is 0.001 to 200, preferably 0.1 to 30; And / or, the width of the central region in the length direction of the electrode coating is greater than or equal to 1 cm.
3. The electrode sheet according to claim 1, characterized in that Each of the edge regions includes a plurality of sub-regions distributed along the length direction of the electrode coating, and in every two adjacent sub-regions, the OI value of the electrode active material of the sub-region close to the central region is smaller than the OI value of the electrode active material of the sub-region far from the central region.
4. The electrode sheet according to claim 3, characterized in that The ratio of the OI value of the electrode active material in the central region to the OI value of the electrode active material in the sub-region closest to the central region is 0.3 to 0.9; and / or, in every two adjacent sub-regions, a ratio of the OI value of the electrode active material in the sub-region close to the central region to the OI value of the electrode active material in the sub-region far from the central region is 0.3 to 0.9; and / or the OI value of the electrode active material of any of the sub-regions is 0.001 to 200, preferably 0.1 to 30; And / or, the width of any of the sub-regions in the length direction of the electrode coating is greater than or equal to 1 cm.
5. The electrode sheet according to any one of claims 1 to 4, characterized in that: The length of the electrode coating is 1 cm to 10 m.
6. The electrode sheet according to any one of claims 1 to 4, characterized in that: The electrode sheet is a negative electrode sheet, and the electrode active material includes graphite.
7. The electrode sheet according to any one of claims 1 to 4, characterized in that: The electrode sheet is a positive electrode sheet, and the electrode active material includes a positive electrode ternary material and / or lithium iron phosphate.
8. The electrode sheet according to any one of claims 1 to 4, characterized in that: The porosity of the electrode coating is 20% to 40%; And / or, the compacted density of the electrode coating is 1.3 g / cm 3 ~2g / cm 3 ; And / or, the surface density of the electrode coating is 200g / m 2 ~800g / m 2 .
9. A method for preparing an electrode sheet according to any one of claims 1 to 8, characterized in that: The following steps are involved: Applying a slurry containing the electrode active material to the surface of the electrode current collector to form a wet film on the surface of the electrode current collector; wherein, along the length direction of the electrode coating, the wet film includes a central region and edge regions located on opposite sides of the central region; Then, a magnetic field of preset strength is applied to the central region and edge region of the wet film, respectively, so that the electrode active materials in the central region and edge region of the wet film respectively reach preset OI values through magnetic field induction; wherein the strength of the magnetic field applied to the central region of the wet film is greater than the strength of the magnetic field applied to the edge region of the wet film; Then, drying and roll pressing are performed to obtain the electrode sheet.
10. The method for preparing an electrode sheet according to claim 9, wherein: The intensity of the magnetic field applied to the central area of the wet film is 0.1T to 20T, preferably 0.2T to 2T.
11. The method for preparing an electrode sheet according to claim 9 or 10, characterized in that: The edge area of the wet film includes multiple sub-areas distributed along the length direction of the wet film. In every two adjacent sub-areas, the intensity of the magnetic field applied to the sub-area close to the central area is greater than the intensity of the magnetic field applied to the sub-area far from the central area.
12. The method for preparing an electrode sheet according to claim 11, wherein: The intensity of the magnetic field applied to any one of the sub-regions of the wet film is 0.1T to 20T, preferably 0.2T to 2T.
13. A battery, characterized in that: The invention relates to an electrode sheet according to any one of claims 1 to 8 or an electrode sheet prepared according to the method for preparing the electrode sheet according to any one of claims 9 to 12.
14. The battery according to claim 13, characterized in that The battery comprises a battery cell, the battery cell comprises a positive electrode sheet and a negative electrode sheet, at least one of the positive electrode sheet and the negative electrode sheet is the electrode sheet according to any one of claims 1 to 8 or the electrode sheet prepared according to the method for preparing the electrode sheet according to any one of claims 9 to 12; The positive electrode sheet includes a positive electrode tab, and the positive electrode tab is located at one end of the battery cell in the length direction; The negative electrode sheet includes a negative electrode tab, and the negative electrode tab is located at the other end of the battery cell in the length direction.
15. An electrical device, characterized in that: A battery comprising the battery according to claim 13 or 14.
Citation Information
Patent Citations
Negative plate and battery
CN113097427A
Negative pole piece, secondary battery and electric device
CN118231565A
Secondary battery and electric device
CN118679595A
Orientation magnetic treatment device and method for graphite coating of negative electrode of battery
CN118681760A
Pole piece and battery with same
CN217544662U
Cited By
Electrode plate and preparation method thereof, battery, battery pack and electric equipment
CN121172053A
Electrode sheet and preparation method therefor, battery, and electric device
WO2026103608A1